Molecular Typing of Turkish Apple Chlorotic Leaf Spot Virus Isolates Based on Partial Coat Protein Gene - Ulubas Serce, C.; Rosner, A. (Phytopathologia Mediterranea, 2006)
Apple chlorotic leaf spot virus (ACLSV) isolates from various hosts and geographic locations in Turkey were molecularly characterized by RFLP, nucleotide sequence analysis and the construction of a phylogenetic tree including ACLSV isolates from GenBank. Based on nucleotide sequence alignment and the phylogenetic tree, we proposed a classification of ACLSV isolates in which isolates were divided into three major groups. The first group contained mainly Far-Eastern isolates, the second group the Hungarian (eastern-European) ACLSV isolates, and the third group, which contained isolates of variable characteristics, was again divided into two subgroups, subgroup I containing mixed European isolates, and subgroup II containing central European isolates. Three representative Turkish ACLSV isolates belonged to the third group; of these, one was from the mixed European cluster (subgroup I) and two from the central European cluster (subgroup II). The nucleotide sequence divergence and geographic origin of the ACLSV isolates were correlated, which indicated the possible extraction of the Turkish isolates.